REPRESENTASI GENDER DALAM PORTRAIT KELUARGA: KAJIANVISUAL PADA MEDIA SOSIAL FACEBOOK - Mecca, Ali; Priyatna, Aquarini; Mulyadi, R.M (Seni Media Rekam ISI Surakarta, 2016)
Family portraits represent gender ideology of a family,and even more widely or asocio-culturally construct society.Family portraits are usually saved and displayed in aconcrete space, on the media wall of a living room, or a family room. Advances intechnology information, bearing new space called the virtual space or cyberspace,havemade it possible for family portraits be displayed in the cyberspace. The researchexplains how gender constructions is displayed through the representation of the familyportraits.This research uses qualitative methods and semiotic approach for its analysis.The results show that gender ideology,normative values,and heteronormativity in thefamily portrait are represented by the position, gestures, clothing, photography, andphotographic composition (aesthetics).Furthermore,is also shown that cyberspace hasbecome a space that manifests gender ideology as well contributes to the familyconstruction. Family portraits do not always display the representation of normativegender roles,but also a family portrait can negotiate with the values that are considerednon-normative ideology.Keywords : Family portrait, representation, and gender